Effects of feeding low protein and low energy diet with protease supplementation on the performance of broiler chickens under two stocking densities - Mohd Taib, Shafeezah (2015)
A study was conducted to determine the effect of supplementing exogenous protease to broiler chickens fed low protein and low energy diets on growth performance, incidence of pododermatitis and antibody production against Newcastle disease vaccination under two stocking densities. A total of 1650 birds were randomly assigned to 60 floor pens with wood shavings as litter material in a closed house into normal (10 birds/m²) and high stocking densities (15 birds/m²). Commencing from day 1-21, bird from each density were given two types of starter diets, normal protein-normal energy (NPNE) and low protein-low energy (LPLE). From day 21-42, birds from each starter diet were given the following three types finisher diets: (i) normal protein-normal energy for both starter and finisher (NPNE-NPNE), (ii) normal protein-normal energy starter and low protein-normal energy finisher (NPNE-LPNE), (iii) normal protein-normal energy starter and low protein-normal energy plus protease finisher (NPNE-LPNEP), (iv) low protein-low energy starter and normal protein-normal energy finisher (LPLE-NPNE), (v) low protein-low energy starter and low protein-normal energy finisher (LPLE-LPNE), and (vi) low protein-low energy starter and low protein-normal energy plus protease finisher (LPLE-LPNEP). Body weight and feed intake, were recorded weekly. Feed conversion ratios were calculated. Daily mortality were recorded. On day 42, 75 birds per diet per density were scored for incidence of pododermatitis. On a similar day, blood samples were collected from 20 birds per diet per density for Newcastle disease antibody titer which was determined by ELISA. There was no significant diet x density interaction for all the parameters. Birds fed LPLE starter diet had significantly lower body weight on day 21 and feed intake during day 1-21 than NPNE. Body weight on day 42, total feed intake (day 1-42) and final FCR (day 1-42) were not significantly affected by diet. Diet had no significant effect on FCR (day1-21) and incidence of pododermatitis (day 42). Birds fed LPLE diets during the starter period had significantly lower Newcastle disease antibody titer than NPNE. High stocking density resulted in significantly lower body weight on day 42, poorer final FCR (day 1-42), higher incidence of pododermatitis, and lower Newcastle disease antibody titer than those stocked at lower density. Neither diet nor stocking density had significant effect on mortality rate. In conclusion, a lower protein and energy diets can be used without any adverse effects on growth performance of broilers chickens. However, LPLE diets may reduce ND antibody production. High stocking density was detrimental to growth performance, incidence of pododermatitis and ND antibody production.